Pengelolaan Tanah Wakaf Masjid terhadap Pengembangan Usaha Produktif dalam Tinjauan Ekonomi Islam - A.Fahrur Rozi; Hari Basuki; Armeita Anik Sukowati (Universitas Nahdlatul Ulama Pasuruan, Indonesia, 2021)
Waqf land management for productive business is a very important thing beneficial for the benefit of the people, starting from the management of productive businesses for facilities worship, education and so on that are still minimally empowered to the maximum. Implementation of waqf land management for productive businesses in village mosques Pagedangan, Turen Malang District, is still simple and traditional. This can seen from the productive waqf assets that grow and develop which are only managed by nazhir sticks to rigid business, lacks innovation, and is a job by-products that are social or voluntary as well as productive waqf assets that grow and Growing is a simple business with little risk. This research conducted in Al-Falah and Baiturrahman mosques. The population in this study amounted to 2 mosques, especially who run productive waqf.